THE SCHOOL MANUALS AS A POSSIBILITY OF RESERACH FOR THE HISTORY OF THE EDUCATION: ELEMENTS FOR A DEFINITION - Samacá Alonso, Gabriel David (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2012)
The present article tries to share a reflection about the school manuals as source for the history of the education. Such an assignment departs from the premise of the need to contribute to a wide and complex definition of the school manual, recognizing it as a cultural factor that can be analyzed from different points of view. The manual can be understood as a pedagogic tool, a good of the publishing world as well as a cultural vector that transports value for the society. Though in the country the research with base in this source began some decades ago, we think that it is necessary to turn the look towards the same one, in order works initiate history-graphic that auscultate the history of the education, particularly the education of the history, from different optical facilitated by the school manuals.Methodologically, this work developed from the critical review of the bibliography specialized in contrast with some school manuals used in the basic secondary education in the decade of the nineties. Besides the abstract proposed elements, it is necessary to remember that the notion of school manual is historical, of there the relevancy of undertaking a characterization of its principal attributes in different historical moments.